Bio-Adrenomedullin and Dipeptidyl Peptidase 3 as Novel Sepsis Biomarkers in the Emergency Department and the Intensive Care Unit: A Narrative Review - Ioannis Ventoulis; Christos Verras; Dionysis Matsiras; Vasiliki Bistola; Sofia Bezati; John Parissis; Effie Polyzogopoulou (Medicina, 2025)
Early recognition and timely treatment of sepsis and septic shock is vital. Despite appropriate management, mortality and morbidity rates remain high. In recent years, many of the research efforts have been directed towards finding novel biomarkers that would rapidly identify, classify and risk-stratify the severity of sepsis in order to achieve prompt and targeted treatment of patients with sepsis and septic shock. Among these biomarkers, adrenomedullin (ADM) in the form of the biologically active fragment (bio-ADM) and dipeptidyl peptidase 3 (DPP3) have recently been in the spotlight. The aim of this narrative review is to summarize current evidence on these two novel biomarkers regarding their clinical utility in diagnosis, prognosis, treatment monitoring and therapy guidance of sepsis and septic shock in the emergency department (ED) and in the intensive care unit (ICU) setting. Bio-ADM seems to be a promising biomarker with respect to the overall management of sepsis (diagnosis, severity prediction, prognosis and treatment monitoring and guidance). On the other hand, DPP3 appears to be useful mainly for sepsis prognosis and for predicting sepsis-induced acute kidney injury. Given their potential clinical utility in sepsis management, the use of these two novel biomarkers, in conjunction with established biomarkers and clinical scores, could lead to the application of refined integrated protocols in the ED and the ICU, which could promptly and effectively inform clinical decision-making in patients presenting with sepsis or septic shock.